Sexually aggressive behavior triggered by parasitic infection – how parasites can influence our personality - Goczol, Marco (Frontiers in Psychiatry, 2025)
Parasitic infections are not only a health problem, but also a psychological and behavioral one. Research shows that certain parasites can influence the personality traits and behavior of infected individuals. Toxoplasma gondii, a well-known parasite, is suspected of increasing the risk of sexually aggressive behavior. This paper examines the links between parasitic infections and personality changes and analyzes the mechanisms by which parasites can affect the nervous system and associated behaviors. The aim is to raise awareness of the psychological and behavioral effects of parasitic infections and to stimulate future research in this area.